THE GEOPOLITICAL LANDSCAPE OF EURASIA UNDER THE PRESSURE OF CASPIAN AND CENTRAL ASIAN POWER PROJECTS - ZHILTSOV, Sergey; ZONN, Igor; MARKOVA, Elena (CENTRAL ASIA AND THE CAUCASUS, 2019)
In the last ten years, the geopolitical situation in the Caspian region and Central Asia has been changing rapidly under the pressure of several factors, the main of them being energy projects realized, in particular, by non-regional states. Oil and gas transportation routes have become a strong instrument of geopolitical impact on the Central Asian and Caspian countries. Through their active involvement, the non-regional states, namely, the U.S., China, and the EU countries, have rechanneled the flows of hydrocarbons and changed the Eurasian geopolitical landscape. Having won this rivalry, China expanded the area of its geopolitical influence. The United States, which since the early 1990s has been working hard to turn the oil and gas flows away from Russia to the West, came second. It changed the directions of Caspian hydrocarbon flows, while the greater part of Central Asian oil and gas is now moved to China. Beijing has become the key partner of the Central Asian and Caspian countries; it determines the nature of their cooperation in the energy sphere and, to a great extent, their foreign policy priorities.